Adhesive as well as preparation method and application thereof
By adding elastic microspheres with core-shell structures and spherical silicon micropowders to the adhesive to form an island-shaped structure, the problem of poor weather resistance of existing adhesives in high and low temperatures and complex environments is solved, and the high weather resistance and mechanical properties of the adhesive are significantly improved.
Patent Information
- Application Number
- CN202510209530.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-29
AI Technical Summary
Existing adhesives have poor weather resistance in high and low temperatures and complex environments, which are prone to cracking and lead to leakage of EC liquid in electrochromic devices, making it difficult to meet the requirements of long-term use.
An adhesive formulation is adopted, including a resin mixture, a reactive diluent, spherical silicon micropowder, initiator, additive and elastic microspheres with core-shell structures. Through the combination of these components, an island-shaped structure is formed to improve the mechanical properties and weather resistance of the adhesive.
It significantly improves the weather resistance and mechanical properties of the adhesive, and can work stably for a long time between -50℃ and 70℃, prevents EC liquid from leaking and failure, and meets the long-term use requirements under harsh environments.
Smart Images

Figure CN119899618A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to an adhesive and a preparation method and application thereof. Background Art
[0002] Electrochromism is a phenomenon in which the optical properties of a material (reflectivity, transmittance, absorptivity, etc.) undergo stable and reversible color changes under the action of an external electric field, which is manifested in the form of reversible changes in color and transparency. Materials with electrochromic properties are called electrochromic materials, and devices made of electrochromic materials are called electrochromic devices.
[0003] EC (electrochromic) glass generally has five thin film layers sandwiched between two substrates, namely a transparent conductive layer, an electrochromic layer, an electrolyte layer, an ion storage layer and another transparent conductive layer. Its working principle is that when a voltage is applied to the electrodes at both ends of the electrochromic element, ions migrate into (or out of) the electrochromic layer under the action of the electric field of the applied voltage, reducing (or increasing) the valence of the electrochromic material. Before reaching equilibrium, the electrochromic material changes color; when equilibrium is reached, the color change of the electrochromic material reaches stability.
[0004] As the core material of the electrochromic rearview mirror, the adhesive plays a key role. In addition to maintaining a low water and oxygen permeability so that the EC liquid in the middle can work stably for a long time, the cured colloid itself is resistant to EC liquid erosion and will not release harmful substances that cause the EC liquid to deteriorate or fail. At the same time, the adhesive should have good thixotropy to facilitate construction.
[0005] Because this material is an automotive-grade product, especially in later application scenarios including high temperature, low temperature, high humidity, high salt and other complex environments, the requirements for encapsulation glue are very high. At the same time, because the ingredients contained in EC liquid are not environmentally friendly, if the leakage caused by sealing failure will cause damage to the environment, therefore, high reliability is a particularly important requirement. The adhesive in the existing technology has poor high and low temperature stability, and is easy to crack under high and low temperatures, resulting in EC liquid leakage, which is difficult to meet the requirements of long-term use in harsh environments.
[0006] Therefore, there is an urgent need for an adhesive with high weather resistance. Summary of the invention
[0007] The main purpose of the present invention is to provide an adhesive and a preparation method and application thereof, so as to solve the problem of poor weather resistance of conventional adhesives in the prior art.
[0008] In order to achieve the above-mentioned object, the present invention provides an adhesive, wherein the raw material components include, by weight: 30 to 70 parts of a resin mixture, 5 to 20 parts of an active diluent, 10 to 30 parts of spherical silicon micropowder, 0.1 to 10 parts of an initiator, 0.1 to 5 parts of an auxiliary agent, and 5 to 30 parts of elastic microspheres with a core-shell structure; the resin mixture includes bisphenol A epoxy resin and bisphenol F epoxy resin.
[0009] Optionally, the mass ratio of the bisphenol A epoxy resin to the bisphenol F epoxy resin is (15-35):(15-35).
[0010] Optionally, the elastic microspheres are acrylic acid copolymers.
[0011] Optionally,
[0012] The epoxy equivalent of the bisphenol A epoxy resin is 130 to 270 g / eq, the viscosity of the bisphenol A epoxy resin is 12000 to 28000 cps, and the bisphenol A epoxy resin is liquid at 25° C.
[0013] The epoxy equivalent of the bisphenol F epoxy resin is 130 to 270 g / eq, the viscosity of the bisphenol F epoxy resin is 6000 to 24000 cps, and the bisphenol F epoxy resin is in liquid state at 25°C.
[0014] Optionally, the active diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
[0015] Optionally, the initiator comprises a mixture of a photoinitiator and a thermal initiator; in the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5):(0.1-5).
[0016] Optionally, the auxiliary agent includes an adhesion promoter, a defoamer, a leveling agent and a dispersant.
[0017] Optionally, the spherical silicon micropowder is spherical silicon micropowder modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
[0018] The present application also provides a method for preparing an adhesive, which is used to prepare the adhesive described in the present application, and the preparation method comprises:
[0019] Step 1, weighing the measured initiator and active diluent, mixing and stirring the two, and obtaining a first mixture after the initiator is completely dissolved;
[0020] Step 2, weighing the measured bisphenol A epoxy resin, bisphenol F epoxy resin, and spherical silicon powder and adding them into a double planetary mixer, premixing at a temperature of 50 to 60° C., and after mixing evenly, adding elastic microspheres with a core-shell structure in small amounts and multiple times to obtain a second mixture;
[0021] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0022] Step 4: Grind and disperse the third mixture in a three-roll mill, and take samples to detect the particle size during the grinding and dispersing process. When the particle size is less than 12 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain the adhesive.
[0023] The present application also provides a use of the adhesive described in the present application in an electrochromic device.
[0024] An adhesive and its preparation method and application according to the technical solution of the present invention, in parts by weight, the raw material components include 30-70 parts of resin mixture, 5-20 parts of active diluent, 10-30 parts of spherical silicon micropowder, 0.1-10 parts of initiator, 0.1-5 parts of auxiliary agent, and 5-30 parts of elastic microspheres with core-shell structure; the resin mixture includes bisphenol A epoxy resin and bisphenol F epoxy resin. The elastic microspheres with core-shell structure can effectively enhance the mechanical properties of the adhesive system. The elastic microspheres with core-shell structure can pre-gel during heating. When interacting with epoxy resin, its shell structure swells and is well compatible with epoxy resin. The core structure is dense and elastically deformed under the action of external force, thereby improving the flexibility and elasticity of the adhesive system. The elastic microspheres are stably grafted as anchor points in the epoxy resin cross-linking polymerization system to form an island-type structure; they can more effectively block water and oxygen and resist internal corrosion. Moreover, the spherical silicon micropowder is more evenly dispersed in the adhesive, which can further enhance the performance of the adhesive after curing. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0026] Figure 1 The present invention is an optional flow chart of an adhesive preparation method according to an embodiment of the present invention. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0028] An adhesive, wherein the raw material components include, by weight: 30 to 70 parts of a resin mixture, 5 to 20 parts of an active diluent, 10 to 30 parts of spherical silicon micropowder, 0.1 to 10 parts of an initiator, 0.1 to 5 parts of an auxiliary agent, and 5 to 30 parts of elastic microspheres having a core-shell structure;
[0029] The resin mixture comprises bisphenol A epoxy resin and bisphenol F epoxy resin.
[0030] Specifically, the resin mixtures are all curable resins. The structure of bisphenol A epoxy resin contains hydroxyl (—CH—OH), ether (—O—) and extremely active epoxy groups. The hydroxyl and ether groups are highly polar, which makes the epoxy molecules produce strong intermolecular forces with the adjacent interface, and the epoxy groups react with the free bonds on the surface of the medium to form chemical bonds with high adhesion. Bisphenol F epoxy resin has low viscosity and good fluidity. The high strength of bisphenol A epoxy resin and the low viscosity of bisphenol F epoxy resin are combined to help improve the strength and elasticity of the prepared adhesive.
[0031] The elastic microspheres with core-shell structure are composed of a core and an outer shell. The core and the outer shell have different chemical compositions and different glass transition temperatures, which create a clear phase separation state. The elastic microspheres with core-shell structure are elastic as a whole and can undergo reversible deformation when subjected to force to buffer external stress. The core-shell elastic microspheres are dispersed in the adhesive matrix as flexible units. At low temperatures, the matrix becomes hard and brittle, and the elastic microspheres can absorb stress by their own elastic deformation, prevent the initiation and expansion of cracks in the adhesive, and maintain the integrity of the bonding interface. The elastic microspheres can buffer the stress of thermal expansion and contraction, so that the system does not crack or debond, which can significantly improve the flexibility of the adhesive, maintain good bonding and mechanical properties in low temperature environments, and improve the tolerance to cold and hot shocks. When heated, the core-shell structure elastomer pre-gels. When in contact with epoxy resin, the outer shell of the elastic microspheres swells and dissolves, and the active groups undergo cross-linking reactions with the epoxy resin to form numerous anchor points. After curing, an island-type structure is constructed. Among them, the "island" is the soft unit provided by the elastic microspheres, and the "sea" is the hard matrix of epoxy resin. When impacted by external force, the soft unit deforms first, dispersing the concentrated impact force to a wider range, consuming energy and preventing the crack from expanding rapidly. The core-shell elastic microspheres are well compatible with epoxy resin, and after curing, the toughness, fracture strength and elongation of the colloid are improved, and the mechanical properties are fully enhanced.
[0032] In addition, bisphenol A epoxy resin and bisphenol F epoxy resin undergo cross-linking polymerization under the action of the initiator, and form an island-like structure together with spherical silicon micropowder and elastic microspheres, which plays a role in blocking water and oxygen from the outside and resisting corrosion from the inside. Spherical silicon micropowder is used as a filler, so that the obtained adhesive also has the characteristics of fast heat dissipation, low CTE and low curing shrinkage, and can improve the insulation ability of the adhesive. Spherical silicon micropowder is a regular sphere, which can be more evenly dispersed in the material and is not easy to agglomerate. The evenly dispersed spherical silicon micropowder can form a stable aggregate network. When it is not subjected to external force, it limits the fluidity of the adhesive, increases viscosity, and prevents flowing and dripping; when subjected to external force, the network structure is destroyed, the viscosity is reduced, and it is easy to construct. After the external force disappears, the network recovers quickly to prevent sagging, so that the rheological properties of the adhesive during storage and construction are more excellent. The adhesive in this application can work stably for a long time between -50℃ and 70℃ and is widely used. The active diluent reduces the viscosity of the adhesive when it is not cured, making it easier to process and use. After curing, it reacts and connects with the mixed resin to form a three-dimensional cross-linked network structure with a higher degree of cross-linking. Additives are commonly used additives in the preparation of adhesives. CTE is the coefficient of thermal expansion.
[0033] In a possible implementation manner, the mass ratio of bisphenol A epoxy resin to bisphenol F epoxy resin is (15-35):(15-35).
[0034] Specifically, the applicant found that under this ratio, the prepared adhesive has better mechanical properties at low temperatures and is not prone to cold brittleness leading to bonding failure.
[0035] In a possible implementation, the elastic microspheres are acrylic acid copolymers.
[0036] Specifically, the elastic microspheres with a core-shell structure in the adhesive are acrylic copolymers, which can pre-gel during the heating process and interact with epoxy resin. From a microscopic structural point of view, the shell structure in the core-shell structure swells and can interact with the epoxy resin when curing, and the elastic microspheres are stably grafted into the epoxy resin system as anchor points to form what we commonly call an island-type structure, in which the shell structure can be well compatible and interact with the resin system, ensuring good dispersion and anchoring of the elastic microspheres in the epoxy resin; while the core structure is relatively denser and can undergo elastic deformation under the action of external forces, thereby greatly improving the mechanical properties of the resin system after curing, especially the compression and tensile properties. There is a significant improvement and reinforcement effect, so that the cured colloid can cope with greater mechanical impacts. At the same time, the core-shell structure elastomer will not experience obvious performance attenuation at low temperatures, which can enhance the mechanical performance of the colloid at the low temperature end, and effectively reduce the probability of low-temperature cold brittleness of the colloid. Acrylic copolymers can further enhance the flexibility and elasticity of the adhesive. The acrylic copolymer with a core-shell structure is one or a mixture of two of STAPHYLOID AC-3355 and ZEFIAC F351.
[0037] In one possible implementation,
[0038] The epoxy equivalent of bisphenol A epoxy resin is 130-270 g / eq, the viscosity of bisphenol A epoxy resin is 12000-28000 cps, and the bisphenol A epoxy resin is liquid at 25°C.
[0039] The epoxy equivalent of the bisphenol F epoxy resin is 130 to 270 g / eq, the viscosity of the bisphenol F epoxy resin is 6000 to 24000 cps, and the bisphenol F epoxy resin is liquid at 25°C.
[0040] Specifically, high Tg bisphenol A epoxy resin and bisphenol F epoxy resin are both liquid at 25°C, which are easier to handle during mixing and processing, and are conducive to uniform mixing and good infiltration. The viscosity of bisphenol A epoxy resin is greater than that of bisphenol F epoxy resin. Bisphenol A epoxy resin is mainly used to improve the strength of adhesives, while bisphenol F epoxy resin is mainly used to improve the fluidity of adhesives.
[0041] Among them, the bisphenol A epoxy resin can be selected from one or more of 828, 828EL, 1510 of Hansen Company, 840, 840-S, 850, 850-S, 850-CRP, 860 of DIC Company, KE-8120 of Cologne Company, YLE-1300A, YLE-1900A, YLE-475, NR-828K-1 of GLK Company, or EP-4100HF, EP-4000S, EP-4000L, EP-4003S, EP-4010L, EP-49-10P, EP-49-10P2 of ADEKA Company. The bisphenol F epoxy resin can be selected from one or more of 830, 830-S, EXA-830LVP, 835, EXA-835LV of DIC, KF-8110 of Cologne, YLE-1300F, YLF-1700F of GLK, EP-4901HF, EP-49-23, EPR-4030 of ADEKA.
[0042] In one possible embodiment, the active diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
[0043] Specifically, using benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether as active diluents of epoxy resin can improve processing performance and optimize the performance of adhesive. Preferably, epoxy glycidyl ether is one or a mixture of bisphenol A epoxy glycidyl ether or bisphenol F epoxy glycidyl ether. Bisphenol A epoxy glycidyl ether or bisphenol F epoxy glycidyl ether has a fast initiation speed, and can be combined with epoxy resin to further increase the crosslinking density, form a tighter three-dimensional network structure, and further improve the stability and weather resistance of the adhesive.
[0044] In a possible implementation, the initiator includes a mixture of a photoinitiator and a thermal initiator; in the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5):(0.1-5).
[0045] Specifically, photoinitiators and thermal initiators can produce a synergistic effect in the reaction. Among them, the photoinitiator absorbs light energy under illumination conditions and converts it into chemical energy, thereby initiating a chemical reaction, while the thermal initiator reacts the active hydrogen with the epoxy group after reaching a certain temperature, and also initiates a chemical reaction. The combination of the two enables the reaction to be carried out under a wider range of temperature and illumination conditions, thereby improving the reaction efficiency. In practical downstream applications, ultraviolet light is first used for curing, and after the adhesive is initially cured, it is heated for deep curing. While the synergistic effect of light and heat can ensure a good curing effect, it is also more convenient for practical application in terms of process. In this application, the photoinitiator is one or more of OXE-01, PAG-002, Omnicat 550, and Omnicat 440. The thermal initiator is an epoxy thermal initiator, which is one or more of EH-4357S, EH-5030S, EH-5057PK, EH-5011S, EH-5046S, EH-2110K from ADEKA, or VDH, VDH-J, UDH, UDH-J from Ajinomoto.
[0046] The appropriate ratio of photothermal initiator helps the colloid to achieve a good curing effect under light and heating conditions, so that the cured colloid has good mechanical properties and high weather resistance.
[0047] In a possible implementation, the auxiliary agent includes one or more of an adhesion promoter, a defoamer, a leveling agent and a dispersant.
[0048] Specifically, the adhesion promoter is evenly dispersed in the resin system, promoting the compatibility of the filler and the resin, and improving the dispersion uniformity of the system. At the same time, as an additive in the adhesive, it can also promote the wetting of the adhesive on the surface of the substrate and improve the wetting of the adhesive on the surface of inorganic metal / glass, which is beneficial to the improvement of the adhesion of the adhesive.
[0049] During the preparation of adhesives, due to changes in temperature, pressure, stirring and other factors, a large number of large bubbles and micron-sized bubbles will exist in the adhesive system. The defoamer added to the system can stably exist in the adhesive system, continue to play a foam-inhibiting role, prevent the generation of new bubbles, and ensure the stability and quality of the adhesive. The leveling agent can improve the fluidity of the adhesive, so that the adhesive can be more evenly covered on the surface of the substrate during coating, and work synergistically with the adhesion promoter to promote the adhesion between the adhesive and the substrate surface. The dispersant can improve the dispersibility of the filler in the adhesive, avoid filler agglomeration and precipitation, and make the adhesive more uniform and stable.
[0050] The defoaming agent is one or more of Defom 2700, 5300, 5500, 6500, 6800, DAPRO AP1622, and the leveling agent is one or more of Levelol 839, Levaslip 810, and Levaslip435.
[0051] The adhesion promoter is one or more of BYK-4500, BYK-4509, BYK-4510, BYK-4511, BYK-4512. The dispersant includes one or more of BYK-9076, DISPERBYK-2152, DISPERBYK-108, DISPERBYK-109, DISPERBYK-145.
[0052] In a possible implementation, the spherical silicon micropowder is spherical silicon micropowder modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
[0053] Specifically, the particle size of the spherical silicon micropowder is 1 to 8 μm. The spherical silicon micropowder modified by the modifier has better compatibility with the resin system in the adhesive.
[0054] The present invention also provides a method for preparing a highly weather-resistant adhesive, which is used in the present application. The preparation method comprises:
[0055] Step 1, weighing the measured initiator and active diluent, mixing and stirring the two, and obtaining a first mixture after the initiator is completely dissolved;
[0056] Step 2, weighing the measured bisphenol A epoxy resin, bisphenol F epoxy resin, and spherical silicon powder into a double planetary agitator, premixing at a temperature of 50-60° C., and after mixing evenly, adding elastic microspheres with a core-shell structure in small amounts multiple times (adding the next time after the previously added microspheres are evenly dispersed) to obtain a second mixture;
[0057] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture;
[0058] Step 4: Grind and disperse the third mixture in a three-roll mill, and take samples to detect the particle size during the grinding and dispersing process. When the particle size is less than 12 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain a highly weather-resistant adhesive.
[0059] Specifically, since the initiator is a powder, it is easy to have uneven dispersion problems when directly mixed with other components. The reactive diluent has a lower viscosity and can well wet and disperse the powder initiator, thereby improving the uniformity of mixing. Therefore, in the present application, the metered initiator and the low-viscosity reactive diluent are first mixed to make the initiator uniformly dissolved in the reactive diluent to obtain a first mixture. Then the metered bisphenol A epoxy resin, bisphenol F epoxy resin and spherical silica powder are premixed in a double planetary agitator, and the temperature is controlled to be 50-60°C. After mixing evenly, a small amount of elastic microspheres with a core-shell structure are added multiple times to obtain a second mixture, wherein when adding the elastic microspheres, the elastic microspheres added previously are uniformly dispersed before adding the next time. The first mixture and the auxiliary agent are added to the second mixture, stirred and mixed to obtain a third mixture, and the third mixture at this time is an adhesive containing spherical silica powder particles and elastic microspheres with a core-shell structure. The third mixture is ground and dispersed using a three-roller mill, and samples are taken several times during the grinding and dispersion process, and tested by a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 12 μm, it can be considered that the adhesive has achieved good dispersion uniformity at this time, and the grinding is stopped. The uniformly dispersed adhesive can reduce the local stress concentration and microcrack formation caused by particle agglomeration, thereby improving the weather resistance and service life of the adhesive. Among them, 30 to 70 parts of a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, 5 to 20 parts of an active diluent, 10 to 30 parts of spherical silica powder, 0.1 to 10 parts of an initiator, 0.1 to 5 parts of an auxiliary agent, and 5 to 30 parts of elastic microspheres with a core-shell structure.
[0060] The present application also provides an application of an adhesive prepared according to the formula in the present application in an electrochromic device.
[0061] Specifically, the adhesive prepared according to the formula in this application is used to adhere the edge gap of the two substrates of EC (electrochromic) glass. Since the adhesive has the function of effectively blocking water and oxygen and resisting internal corrosion, it is ensured that the EC liquid of the two substrates will not be corroded by external water and oxygen. In addition, the adhesive in this application is resistant to EC liquid corrosion and will not release harmful substances to cause EC liquid to deteriorate or fail. Under low or high temperature conditions, it can still maintain stable performance for a long time, ensuring that the EC liquid will not leak or fail.
[0062] The present invention is further illustrated by the following examples.
[0063] Example
[0064] By weight, 25% bisphenol A epoxy resin, 25% bisphenol F epoxy resin, 10% active diluent, 10% elastic microspheres with core-shell structure, 24% spherical silica powder, 3.5% photoinitiator, 1.0% thermal initiator, 0.5% adhesion promoter, 0.3% defoamer, 0.2% leveling agent and 0.5% dispersant.
[0065] Step 1: Mix and stir 3.5% of a photoinitiator, 1.0% of a thermal initiator and 10% of a reactive diluent, and obtain a first mixture after the initiator is completely dissolved;
[0066] Step 2: Add 25% of bisphenol A epoxy resin, 25% of bisphenol F epoxy resin and 24% of surface modified spherical silica powder into a double planetary mixer, premix at a temperature of 50-60° C., mix well, and then add 10% of elastic microspheres with a core-shell structure in small amounts several times to obtain a second mixture;
[0067] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring evenly to obtain a third mixture;
[0068] Step 4: Grind and disperse the third mixture in a three-roll mill, take samples several times during the grinding and dispersion process, and test it with a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 12 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain adhesive 1, and the syringe can be degassed for a second time before testing.
[0069] The physical properties of the prepared adhesive 1 are as follows:
[0070] In the uncured state: viscosity = 132987mPa·s;
[0071] In the cured state: hardness = 81D (Shore), adhesion = 11.34Mpa, elongation at break = 7.15%, tensile strength = 36.58Mpa. The number of hot and cold shock cycles (-55 to 100°C, switching once every 30 minutes) is greater than 600 times.
[0072] Comparative Example
[0073] By weight, 25% bisphenol A epoxy resin, 25% bisphenol F epoxy resin, 10% active diluent, 34% spherical silica powder, 3.5% photoinitiator, 1% thermal initiator, 0.5% adhesion promoter, 0.3% defoamer, 0.2% leveling agent and 0.5% dispersant.
[0074] Step 1: Mix and stir 3.5% of a photoinitiator, 1.0% of a thermal initiator and 10% of a reactive diluent, and obtain a first mixture after the initiator is completely dissolved;
[0075] Step 2: adding 25% of bisphenol A epoxy resin, 25% of bisphenol F epoxy resin and 34% of spherical silicon powder into a double planetary mixer, and premixing at a temperature of 50-60° C. to obtain a second mixture;
[0076] Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring evenly to obtain a third mixture;
[0077] Step 4: Grind and disperse the third mixture in a three-roll mill, take samples several times during the grinding and dispersion process, and test it with a scraper fineness meter. When the test results show that the size of the largest particles or agglomerates is less than 12 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain adhesive 2, and the syringe can be degassed for a second time before testing.
[0078] The physical properties of the prepared adhesive 2 are as follows:
[0079] In the uncured state: viscosity = 103428 mPa·s;
[0080] In the cured state: hardness = 60D (Shore), adhesion = 1.12Mpa, elongation at break = 1.05%, tensile strength = 6.33Mpa, number of hot and cold shock cycles (-55 to 100°C, switching once every 30mins) 148 times.
[0081] It can be seen from the above embodiments and comparative examples that the adhesive with elastic microspheres having a core-shell structure has good resistance to cold and heat shock, and remains leak-proof for more than 600 cycles, while the control group without elastic microspheres having a core-shell structure can only last for 148 cycles, which is a large gap from the experimental group. This shows that adding elastic microspheres having a core-shell structure to the adhesive can significantly improve the weather resistance of the adhesive. At the same time, in terms of performance indicators, the experimental group is also significantly better than the control group, and it can be seen that the addition of elastic microspheres can significantly increase the mechanical properties of the material.
[0082] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An adhesive, characterized in that: The raw material components include, by weight: 30 to 70 parts of a resin mixture, 5 to 20 parts of an active diluent, 10 to 30 parts of spherical silicon micropowder, 0.1 to 10 parts of an initiator, 0.1 to 5 parts of an auxiliary agent, and 5 to 30 parts of elastic microspheres having a core-shell structure; The resin mixture comprises bisphenol A epoxy resin and bisphenol F epoxy resin.
2. An adhesive according to claim 1, characterized in that: The mass ratio of the bisphenol A epoxy resin to the bisphenol F epoxy resin is (15-35):(15-35).
3. An adhesive according to claim 1, characterized in that: The elastic microspheres are acrylic acid copolymers.
4. An adhesive according to claim 1, characterized in that: The epoxy equivalent of the bisphenol A epoxy resin is 130 to 270 g / eq, the viscosity of the bisphenol A epoxy resin is 12000 to 28000 cps, and the bisphenol A epoxy resin is liquid at 25° C. The epoxy equivalent of the bisphenol F epoxy resin is 130 to 270 g / eq, the viscosity of the bisphenol F epoxy resin is 6000 to 24000 cps, and the bisphenol F epoxy resin is in liquid state at 25°C.
5. The adhesive according to claim 1, characterized in that: The active diluent is epoxy glycidyl ether, and the epoxy glycidyl ether is one or more combinations of benzyl glycidyl ether, allyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, C12-14 glycidyl ether, bisphenol A epoxy glycidyl ether and bisphenol F epoxy glycidyl ether.
6. An adhesive according to claim 1, characterized in that: The initiator comprises a mixture of a photoinitiator and a thermal initiator; in the initiator mixture, the mass ratio of the photoinitiator to the thermal initiator is (0.1-5): (0.1-5).
7. The adhesive according to claim 1, characterized in that: The auxiliary agents include adhesion promoters, defoamers, leveling agents and dispersants.
8. The adhesive according to claim 1, characterized in that: The spherical silicon micropowder is spherical silicon micropowder modified by a modifier; the modifier includes one of a silane coupling agent, polyacrylamine, POSS, titanate, fatty acid, organic acid and inorganic acid.
9. A method for preparing an adhesive, characterized in that: Applicable to the adhesive according to any one of claims 1 to 8, wherein the preparation method comprises: Step 1, weighing the measured initiator and active diluent, mixing and stirring the two, and obtaining a first mixture after the initiator is completely dissolved; Step 2, weighing the measured bisphenol A epoxy resin, bisphenol F epoxy resin, and spherical silicon powder and adding them into a double planetary mixer, premixing at a temperature of 50 to 60° C., and after mixing evenly, adding elastic microspheres with a core-shell structure in small amounts and multiple times to obtain a second mixture; Step 3, adding the first mixture and the auxiliary agent into the second mixture, stirring, to obtain a third mixture; Step 4: Grind and disperse the third mixture in a three-roll mill, and take samples to detect the particle size during the grinding and dispersing process. When the particle size is less than 12 μm, stop grinding to obtain a fourth mixture; vacuum degas the fourth mixture and fill it into a syringe to obtain the adhesive.
10. Use of the adhesive according to any one of claims 1 to 8 in an electrochromic device.